Efficiency of Renal Replacement Therapy for Cardiogenic Shock Complicated by Multiorgan Dysfunction - L. S. Barbarash; A. N. Popkov; V. Yu., Kheraskov; G. P. Plotnikov; D. L. Shukevich; E. V. Grigoryev (Общая реаниматология, 2011)
Objective: to analyze the efficiency of renal replacement therapy (RRT) for acute myocardial infarction complicated by cardiogenic shock and multiorgan dysfunction. Subjects and methods. Sixty-six patients with acute myocardial infarction complicated by cardiogenic shock were enrolled in the study. The postoperative period after coronary angioplasty was complicated by multiorgan dysfunction in all the patients. Results. The efficiency of postoperative RRT in abolishing systemic inflammatory response was evaluated. Conclusion. RRT incorporated within the first 12 hours following coronary angioplasty into an intensive care package for acute myocardial infarction complicated by cardiogenic shock has an effect in preventing multiorgan dysfunction and assists in reducing deaths due to extracardiac causes inflammatory response. Key words: acute myocardial infarction, cardiogenic shock, multiorgan dysfunction, renal replacement therapy.